Table of Content - - (Journal of medical and pharmaceutical sciences, 2023)
Table of Content:1. The effect of using some medicinal plants in the treatment of pain and inflammation in Abdali farms in the State of KuwaitMrs. Enas Abdulaziz Alsarawi2. Lifestyle and nutrition of the Gulf countries students living in the UKDr. Manal Amro Almughamisi, Dr. Ameerah Mohammed Khairi Almaski3. Childhood and Adolescent Overweight, Obesity and Socio-Economic Circumstances in The Gulf Cooperation Council Countries: A Systematic ReviewDr. Manal Amro Almughamisi, Dr. Majella O’Keeffe, Prof. Seeromanie Harding4. Assessment of Hospitalised Patient Satisfaction with Nursing Care in the Gynaecology and Obstetrics Department of Benghazi Medical Center, LibyaLecturer / Fatma Abdalla Atitalla Omar , Lecturer / Fathi Saad Mustafa , Dr. Randa Mahmoud Gadalla Elamrony5. Assessing knowledge of Pediatric Diabetes Mellitus among Nurses at Turaif General Hospital, Saudi ArabiaZiyad Osailan Alruwaili , Waajid Awad Alanzi, Ayesh Hussein Alhazmi, Mansur Mohammd Alrwaili6. Job Satisfaction and Associated Factors among Healthcare Workers at King Fahad University Hospital in Al-KhobarMaram Habib Hussain Alali
Keywords: Journal of Medical and Pharmaceutical Sciences